Combinatorial Design of Isoform‐Selective N‐Alkylated Benzimidazole‐Based Inhibitors of Carbonic Anhydrases. Issue 19 (4th July 2017) - Čapkauskaitė, Edita; Linkuvienė, Vaida; Smirnov, Alexey; Milinavičiūtė, Goda; Timm, David D.; Kasiliauskaitė, Aistė; Manakova, Elena; Gražulis, Saulius; Matulis, Daumantas
Abstract: Human carbonic anhydrases comprise a family of isoforms that form structurally similar active site and thus it is difficult to design inhibitors that would selectively inhibit the targeted isoform and leave uninhibited all remaining ones. Most common inhibitors are aromatic sulfonamides that strongly bind and inhibit CAs, but usually with limited selectivity towards a targeted isoform. However, sometimes seemingly minor changes in the inhibitor structure may cause significant increase or decrease in affinity towards a CA isoform. Here, the affinities of previously designed N ‐alkylated benzimidazoles were determined to all active human CA isoforms. This combinatorial approach yielded several compounds that were highly selective for CA VA. Intrinsic affinities were determined by subtraction of the binding‐linked protonation reactions that, together with the X‐ray crystallographic structures revealing the arrangement of the inhibitors in the active site, help in the design of inhibitors exhibiting subnanomolar affinities and improved selectivities towards a particular CA isoform. Abstract : Combinatorially designed N ‐alkylated benzimidazole affinities were determined towards all 12 catalytically active human CA isoforms. The approach yielded several compounds that were highly selective for CA VA. Intrinsic affinities were determined by subtraction of the binding‐linked protonation reactions that, together with the X‐ray crystallographic structures revealing the arrangement of the inhibitors in the active site, help in the design of inhibitors with improved selectivities towards a desired CA isoform.